Analisis Implementasi Strategi Perencanaan Pajak Penghasilan Badan sebagai Upaya Penghematan Beban Pajak pada PT Anggada Indo Asia - Amelia Chantika Fati’ah; Syamsul Bahri Arifin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of corporate income tax (PPh) planning strategies at PT Anggada Indo Asia in order to achieve tax burden efficiency. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results show that the company has not fully implemented tax planning in accordance with tax regulations, as evidenced by fiscal corrections on several expense items that do not comply with tax rules. Based on these findings, the recommended tax planning strategies include improving compliance with tax regulations, preparing more comprehensive documentation, and transferring non-deductible expenses to forms that are fiscally recognized. With the implementation of this strategy, the company successfully saved tax expenses amounting to IDR 2,816,430, which equates to a 2.4% efficiency from the total tax liability. This result demonstrates that effective tax planning can be a legitimate tool to reduce tax burdens while also improving the efficiency of the company’s financial management. Therefore, applying good tax planning strategies not only contributes to tax savings but also helps the company achieve more optimal financial management in compliance with applicable tax regulations.